The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3390/ma7010244
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution and Dynamic Softening Mechanisms of Al-Zn-Mg-Cu Alloy during Hot Compressive Deformation

Abstract: The hot deformation behavior and microstructural evolution of an Al-Zn-Mg-Cu (7150) alloy was studied during hot compression at various temperatures (300 to 450 °C) and strain rates (0.001 to 10 s−1). A decline ratio map of flow stresses was proposed and divided into five deformation domains, in which the flow stress behavior was correlated with different microstructures and dynamic softening mechanisms. The results reveal that the dynamic recovery is the sole softening mechanism at temperatures of 300 to 400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…Recently, CDRX was also reported in aluminum alloys [41]. This mechanism differs from that of DDRX, new grains are formed progressively within the deformed original low angle grains from a continuous increase of subgrains with low misorientations, as a result of the accumulation of dislocations in low angle boundaries [38][39][40][41].…”
Section: Compression Characteristics and Activation Energy Of Deformamentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, CDRX was also reported in aluminum alloys [41]. This mechanism differs from that of DDRX, new grains are formed progressively within the deformed original low angle grains from a continuous increase of subgrains with low misorientations, as a result of the accumulation of dislocations in low angle boundaries [38][39][40][41].…”
Section: Compression Characteristics and Activation Energy Of Deformamentioning
confidence: 98%
“…The DDRX was observed in Al alloys, which involves development of high angle grain boundaries via nucleation and growth of new grains that typically initiate at original grain boundaries, boundaries of dynamically recrystallized grains and boundaries created during deformation [39]. Recently, CDRX was also reported in aluminum alloys [41]. This mechanism differs from that of DDRX, new grains are formed progressively within the deformed original low angle grains from a continuous increase of subgrains with low misorientations, as a result of the accumulation of dislocations in low angle boundaries [38][39][40][41].…”
Section: Compression Characteristics and Activation Energy Of Deformamentioning
confidence: 99%
“…Li [5] studied the deformation behaviors of Ag-containing 2519 aluminum alloy by isothermal compression and found DRX when the strain rate was 10 s -1 and the temperature was higher than 300 o C. Liu [6] reported that dynamic recrystallization of Al-Cu-Mg-Ag alloy occurred at low Z values and the tendency of dynamic recrystallization enhanced with decreasing Z value. Huang [7] [8,9].…”
Section: Introductionmentioning
confidence: 98%
“…The age-hardenable 7xxx series Al alloys can be divided into medium strength Al-Zn-Mg system and high strength Al-Zn-Mg-Cu system [1][2][3][4][5][6]. Nowadays, 7xxx series alloys are being used in the aerospace and high-speed train system for structural components due to their high strength/weight ratio [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%